Implementation of Sheikh Ahmad Rifa'i's Sufism Values ​​at the Miftahul Muhtadin Pati Islamic Boarding School - Luluk Atul Janah; Abdul Bashith; Akhmad Nurul Kawakip (al-Afkar, Journal For Islamic Studies, 2025)
The current decline in the morals and morals of the younger generation is still a crucial and very worrying problem that needs a solution. Syekh Ahmad Rifa'i introduced simple Sufism teachings which can be a solution for improving the morals of young people. The values contained in Sufism need to be applied massively so that the formation of noble morals can be achieved. Therefore, the objectives of this research are: 1). knowing the application of the values of Sufism to Syekh Ahmad Rifa'i at the Miftahul Muhtadin Pati Islamic Boarding School 2). find out the implications of Sufism values for the implementation of education at the Miftahul Muhtadin Pati Islamic Boarding School. This research uses field research with a descriptive qualitative approach. Research data is primary and secondary data. Data collection techniques were carried out using observation, interviews and documentation methods. Meanwhile, data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the research show that the implementation of Sufism values carried out at the Miftahul Muhtadin Pati Islamic Boarding School includes three forms, namely introduction and understanding, exemplary educators, and training and habituation. Meanwhile, the resulting implications have a positive impact in the form of forming students with noble morals, high spiritual intelligence, and awareness to get closer to Allah SWT.